Prediction of sepsis-related outcomes in neonates through systematic genotyping of polymorphisms in genes for innate immunity and inflammation: a narrative review and critical perspective - Carvalho, Juliana Kilesse (2013)
CONTEXT AND OBJECTIVE: Neonatal sepsis is associated with premature birth and maternal infection. Large-scale studies seek to define markers that identify neonates at risk of developing sepsis. Here, we examine whether the scientific evidence supports systematic use of polymorphism genotyping in cytokine and innate immunity genes, to identify neonates at increased risk of sepsis. DESIGN AND SETTING: Narrative literature review conducted at Fernandes Figueira Institute, Brazil. METHODS: The literature was searched in PubMed, Embase (Excerpta Medica Database), Lilacs (Literatura Latino-Americana e do Caribe em Ciências da Saúde), SciELO (Scientific Electronic Library Online) and Cochrane Library. From > 400,000 references, 548 were retrieved based on inclusion/exclusion criteria; 22 were selected for detailed analysis after quality assessment. RESULTS: The studies retrieved addressed the impact of gene polymorphisms relating to immune mechanisms (most often TNF-a, LT-a, IL-6, IL-1β, IL-1ra, L-selectin, CD14 and MBL) or inflammatory mechanisms (ACE and angiotensin II receptors; secretory PLA2; and hemostatic factors). Despite initial reports suggesting positive associations between specific polymorphisms and increased risk of sepsis, the accumulated evidence has not confirmed that any of them have predictive power to justify systematic genotyping. CONCLUSIONS: Sepsis prediction through systematic genotyping needs to be reevaluated, based on studies that demonstrate the functional impact of gene polymorphisms and epidemiological differences among ethnically distinct populations.